2021
DOI: 10.1007/s13399-021-01932-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biodegradation of organic waste treated by environmental fungal isolates with higher cellulolytic potential

Abstract: Lignocellulosic biomass from agricultural waste seems promising feedstock for biofuel production; however, its degradation to fermentable sugars is challenging. Interestingly, fungi have shown substantial potential for the breakdown of lignocellulosic biomass and thus could be employed in lignocellulose-based biorefinery. Aiming at this, the current study was focused on screening the novel cellulolytic fungi from the surrounding environment. The preliminary molecular/morphological screening of 107 samples narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Then, five grams of each dry, milled (0.5–1 cm) substrate were mixed with 2.5 g yeast extract/L deionised water, with the moisture level maintained at 60%. Next, a fungal spore suspension (10 6 cells/mL) was aseptically inoculated in flasks (5%; w/v of the substrate) and incubated at 30 °C for 5 days [ 91 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, five grams of each dry, milled (0.5–1 cm) substrate were mixed with 2.5 g yeast extract/L deionised water, with the moisture level maintained at 60%. Next, a fungal spore suspension (10 6 cells/mL) was aseptically inoculated in flasks (5%; w/v of the substrate) and incubated at 30 °C for 5 days [ 91 ].…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of fungal enzymes is the rst and most important step in enzyme technology, as it determines the process's economic viability. A considerable number of cellulases have been produced from fungal species such as Aspergillus or nature [8], Penicillium sp [9], Aspergillus terries MS [10], Aspergillus terries MI [11,12], Aspergillus niger and Rhizopes [13,14], Trichoderma viride [13], and Trichoderma longibrachiatum [15].…”
Section: Introductionmentioning
confidence: 99%
“…As the most abundant carbohydrate in nature, cellulose is an essential class of renewable resources (Li et al 2021). Its biotransformation degradation technology has become a research hotspot for both energy and the environmental sciences because of its high degradation efficiency, low energy consumption, safety, and lack of pollution (Awais et al 2021). However, little research has been reported on the screening and performance of low-temperature resistant cellulose-degrading strains.…”
Section: Introductionmentioning
confidence: 99%